The Fusaric Acid Derivative qy17 Inhibits Staphylococcus haemolyticus by Disrupting Biofilm Formation and the Stress Response via Altered Gene Expression - Wang, Bing; Song, Chao-Rong; Zhang, Qing-Yan; Wei, Peng-Wei; Wang, Xu; Long, Yao-Hang; Yang, Yong-Xin; Liao, Shang-Gao; Liu, Hong-Mei; Xu, Guo-Bo (Frontiers in Microbiology, 2022)
Staphylococcus haemolyticus (S. haemolyticus) is the second most commonly isolated Coagulase-negative staphylococci (CoNS) in patients with hospital-acquired infections. It can produce phenol-soluble modulin (PSM) toxins and form biofilms. Compared with the wealth of information on Staphylococcus aureus and Staphylococcus epidermidis, we know very little about S. haemolyticus. There is an urgent need to find an effective preparation to combat the harm caused by S. haemolyticus infection. Chinese herbs have been utilized to cure inflammation and infectious diseases and have a long history of anticancer function in China. Here, we modified fusaric acid characterized from the metabolites of Gibberella intermedia, an endophyte previously isolated from Polygonum capitatum. This study shows that fusaric acid analogues (qy17, qy20) have strong antibacterial activity against S. haemolyticus. In addition, crystal violet analysis and scanning electron microscopy observations demonstrated that qy17 inhibits biofilm formation and disrupts mature biofilms of S. haemolyticus in a dose-dependent manner. Besides, it reduced the number of live bacteria inside the biofilm. Furthermore, the antibiofilm function of qy17 was achieved by downregulating transcription factors (sigB), transpeptidase genes (srtA), and bacterial surface proteins (ebp, fbp) and upregulating biofilm-related genes and the density-sensing system (agrB). To further elucidate the bacteriostatic mechanism, transcriptomics analysis was carried out. The following antibacterial mechanisms were uncovered: (i) The inhibition of heat shock (clpB, groES, groL, grpE, dnaK, dnaJ)-, oxidative stress (aphC)- and biotin response (bioB)-related gene expression resulted in S. haemolyticus being unable to compensate for various stress conditions, thereby affecting bacterial growth; (ii) A reduction in the expression of phenol-soluble modulin PSM-beta (PSMβ1, PSMβ2, PSMβ3) toxin- and Clp protease (clpP, clpX)-related genes, this could have major implications in the treatment of diseases caused by S. hemolytica infections. Our research reveals for the first time that fusaric acid derivatives inhibit the expression of biofilm formation-related effectors and virulence genes of S. haemolyticus. These findings provide new potential drug candidates for hospital-acquired infections caused by S. haemolyticus.